PENILAIAN DAYA TARIK WISATA AI SIPATN LOTUP PERUNTAN DI DESA SAPEKABUPATEN SANGGAU - Efendi, Yulius; Rifanjani, Slamet; Siahaan, Sarma (JURNAL HUTAN LESTARI, 2019)
Ecotourism is one of the tourism activities that are environmentally sound by prioritizing aspects of nature conservation, aspects of socio-cultural empowerment of local communities and aspects of learning and education. Attractiveness is a factor that makes people want to visit and see directly to a place that has such an attraction. Ai Sipatn Lotus Peruntan is a hot spring in Cape Village in the protected forest area. During this time, many local villagers used Ai Sipatn Lotus Peruntan for recreation and for skin treatment because they believed they could cure skin diseases. The potential of Ai Sipatn Lotus Peruntan can be developed for Ecotourism Attractiveness, but there is not much presence of Ai Sipatn Lotus Peruntan, new visitors to some of the surrounding communities. Therefore the attractiveness of hot water sources makes people less aware of the information. The research objective is to assess the hot water attraction of Ai Sipatn Lotus Perun. The study was conducted in Cape Village, Jangkang Sub-District, Sanggau District for Â± 3 weeks in April 2018. The research method used a survey method with the help of a questionnaire. Determination of respondents by accidental sampling. Data analysis by scoring and weighting refers to the ADO-ODTWA guideline of the 2003 PHKA Director-General. Assessment results of Ai Sipatn Hot Springs Lotus Peruntan Tourism Attraction on value elements of 157.33 After being obtained multiplied by the weight value of the assessment criteria of Ai Hot Springs tourist attraction Sipatn Lotus Peruntan which has a weight of 6, so that the value obtained for the assessment criteria for Ai Sipatn Lotus Peruntan Hot Springs tourist attraction to 157.33 x 6 = 943.98 shows that in terms of attractiveness, ODTWA Ai Sipatn lot up peruntan has a value of B or has good appeal.Keywords: attraction, hot water, natural attraction, nature tourism